Correlation between thermal parameters, structures, dendritic spacing and corrosion behavior of Zn-Al alloys with columnar to equiaxed transition - Ares, Alicia Esther (2008)
The columnar to equiaxed transition (CET) has been examined for many years and the significance of CET has been treated in several articles. Experimental observations in different alloy systems have shown that the position of the transition is dependent on parameters like cooling rate, velocity of the liquidus and solidus fronts, local solidification time, temperature gradients and recalescence. The dendritic structure in alloys results in microsegregation of solute species which affects significantly the mechanical properties of the material. The main parameters characterizing the microstructure and the length range of microsegregation is the spacing which is classified as primary, secondary and tertiary. Properties like mechanical resistance and ductility are influenced by the dimensions and continuity of the primary branches, while the secondary and tertiary branches permit the isolation of interdendritic phases which can deteriorate the mechanical behavior of the material. Since the morphology and dimensions of the dendritic structure is related to the solidification parameters mentioned above, for each type of alloy it is essential to correlate dimensions and solidification conditions in order to control the structure. The objective of the present research consists on studying the influence of solidification thermal parameters with the type of structure (columnar, equiaxial or with the CET); and with grain size and dendritic spacing (primary and secondary) in Zn-Al (ZA) alloys (Zn-4 wt%Al, Zn-16 wt%Al and Zn-27 wt%Al, weight percent). Also, correlate the thermal parameters, type of structure, grain size and dendritic spacing with the corrosion resistance of these alloys. © 2007 Elsevier B.V. All rights reserved.